2010
DOI: 10.1007/s12104-010-9212-2
|View full text |Cite|
|
Sign up to set email alerts
|

Backbone chemical shift assignments of the acyl-acyl carrier protein intermediates of the fatty acid biosynthesis pathway of Plasmodium falciparum

Abstract: We report the backbone chemical shift assignments of the acyl-acyl carrier protein (ACP) intermediates of the fatty acid biosynthesis pathway of Plasmodium falciparum. The acyl-ACP intermediates butyryl (C(4)), -octanoyl (C(8)), -decanoyl (C(10)), -dodecanoyl (C(12)) and -tetradecanoyl (C(14))-ACPs display marked changes in backbone HN, C(alpha) and C(beta) chemical shifts as a result of acyl chain insertion into the hydrophobic core. Chemical shift changes cast light on the mechanism of expansion of the acyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2025
2025

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…75 In P. falciparum acyl-ACP the hydrophobic cavity appears to be able to enclose up to a 12 carbon chain. 76,77 Insertion of the acyl chain induces a similar structural change to that seen in other carrier proteins, with helix III 0 moving away from helix II to enlarge the hydrophobic cavity as the acyl chain increases in length. MD simulations of b-hydroxydecanoyl-ACP suggested that substrate delivery was between a-helices II and III 0 .…”
Section: Acyl Acp Structuresmentioning
confidence: 78%
“…75 In P. falciparum acyl-ACP the hydrophobic cavity appears to be able to enclose up to a 12 carbon chain. 76,77 Insertion of the acyl chain induces a similar structural change to that seen in other carrier proteins, with helix III 0 moving away from helix II to enlarge the hydrophobic cavity as the acyl chain increases in length. MD simulations of b-hydroxydecanoyl-ACP suggested that substrate delivery was between a-helices II and III 0 .…”
Section: Acyl Acp Structuresmentioning
confidence: 78%